"Alexa, lock my front door": An empirical study on factors affecting consumer's satisfaction with VCA‐controlled security devices. Issue 1 (31st October 2022) - Moriuchi, Emi
Abstract: Voice conversation agents (VCAs) have moved beyond simple tasks such as information gathering. The integration of VCAs in smart technologies for security has grown in the consumer market. This paper investigates consumers' motivation to use smart technologies controlled by voice conversational agents and how that impacts their perceived hedonic and utilitarian value, which eventually leads to their satisfaction with smart technologies usage. Two cross‐sectional studies and a netnography were conducted. The findings showed that the variables measuring technology acceptance mediate the relationship between consumers' motivation and the perceived value of the VCA‐controlled smart technologies. Study 1 results show that ease of use and usefulness of the VCA‐controlled smart technologies have a more substantial mediating effect between motivation and hedonic value than utilitarian value. For study 2, results show that the mediators had a stronger influence on hedonic and utilitarian values for outdoor voice conversational agent‐controlled smart technologies than indoor smart technologies. Study 3 showed that smart technologies have both risks and benefits and depend on whether they are being used for themselves or others. The results suggest that marketers need to consider consumer's emphasis on the products' features including its ease of use and usefulness, and strategically complement it with consumers' prevention and promotion focus for each product.